Detail process charting : speaking the language of process - Graham, Ben B. (John Wiley & Sons. Inc., 2004)
Praise for Detail Process Charting''A must-read for any competitive organization, Detail Process Charting: Speaking the Language of Process provides a comprehensive, yet clear, explanation of how to utilize one of the most powerful tools available to improve work processes.